2022
DOI: 10.3390/nu14132589
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Treatment Prevents Uremia-Induced Reductions in Aortic microRNA-145 Attenuating Osteogenic Differentiation despite Hyperphosphatemia

Abstract: In chronic kidney disease, systemic inflammation and high serum phosphate (P) promote the de-differentiation of vascular smooth muscle cells (VSMC) to osteoblast-like cells, increasing the propensity for medial calcification and cardiovascular mortality. Vascular microRNA-145 (miR-145) content is essential to maintain VSMC contractile phenotype. Because vitamin D induces aortic miR-145, uremia and high serum P reduce it and miR-145 directly targets osteogenic osterix in osteoblasts, this study evaluated a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…In our case, the specific role of VSMC VDR is assessed, clearly showing that lack of vitamin D signaling in this cell type leads to lower VC. There is also an apparent discrepancy between our results and those of Carrillo-Lopez et al 47 In their study, the authors showed that treatment of CKD mice with vitamin D induced an increase in miR-145 in the arteries. However, in their study, they administered the synthetic VDRA (vitamin D receptor agonist) paricalcitol (19-nor 1,25[OH] 2 D 2 ), whereas we use the animal form of active vitamin D (1,25D).…”
Section: Discussioncontrasting
confidence: 99%
“…In our case, the specific role of VSMC VDR is assessed, clearly showing that lack of vitamin D signaling in this cell type leads to lower VC. There is also an apparent discrepancy between our results and those of Carrillo-Lopez et al 47 In their study, the authors showed that treatment of CKD mice with vitamin D induced an increase in miR-145 in the arteries. However, in their study, they administered the synthetic VDRA (vitamin D receptor agonist) paricalcitol (19-nor 1,25[OH] 2 D 2 ), whereas we use the animal form of active vitamin D (1,25D).…”
Section: Discussioncontrasting
confidence: 99%
“…On Day 3 of incubation, OCN expression in the miR-141-3p mimic group was not significantly lower than that in the mimic-NC group. This result may be related to the role of OCN as an expression marker in the late stage of osteogenesis, making 3-day incubation insufficient for the fluctuation of OCN expression during complete osteogenesis (Carrillo-López et al, 2022). DSPP is an odontoblast-specific gene, and mutations in the human.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are comprised of a group of endogenous non‐coding small RNAs with a length of 18–25 nt, regulate gene expression following transcription, and participate in multiple physiological and pathological processes (e.g., cell proliferation, differentiation, and apoptosis) (Carrillo‐López et al, 2022; He et al, 2020; Liu et al, 2021). MiR‐141‐3p, as a member of the miR‐200 family, plays a key role in the multiple cellular process (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies, for instance, a recent study showed that obese and non-obese type 2 diabetes mellitus (T2DM) with deficiencies of vitamin D presented an up-regulation of miR-145-5p in plasma (5.91-fold) compared with those with insufficiency (4.61-fold) and sufficiency (4.29-fold) [62]. Moreover, recently, it was demonstrated that miR-145-5p is regulated by the vitamin D 3 treatment in gastric cancer cells [63] and in aortic tissue [64]. Evidence suggests that the supplementation of vitamin D 3 may induce the reduction in expression of miR-145-5p, improving asthma status.…”
Section: The Role Of Microrna-145 In Asthma and Its Modulation By Vit...mentioning
confidence: 99%